The Stent Evolution in Colo-Rectal Emergencies - Andrea Cavallaro; Giorgio Maria Paolo Graziano; Marco Cavallaro; Antonino Graziano (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Introduction: The appearance of a framework for occlusive colorectal tumor raises complex issues and difficult. We need to ensure a resumption of normal bowel function in patients often in extreme conditions. Emergency surgery flounders in a derivation and a resection with restoration of intestinal transit. The progress of digestive endoscopy can now make available a medical procedure can solve the framework occlusive both as palliation both as a bridge to safer surgery. The purpose of this study is to evaluate the indications and limitations of the method of colon prosthesis with self expandable stents. Materials and methods: From 1996 to 2004 at the surgical clinic III - University Policlinic of Catania - were performed 162 interventions for colorectal pathology of which 82 for benign disease and the remaining 80 for malignant disease. In four of these cases of neoplastic occlusions (one in which the precarious clinical condition and high anesthetic risk high - ASA 5 - in a metastatic patient made problematic the surgical indication and 3 in which the significant intestinal distension induced to believe priority prosthetic re-canalization) recovery of bowel function was made possible with an attachment of metal self-expandable prosthesis. These 4 patients were compared with the same number of patients in overlapping conditions in which the re-channeling has been obtained by surgical methods in emergency. This has highlighted, despite its low numbers, at least a trend of lower risk in favor of the prosthesis, while recognizing that the endoscopic procedure involves a considerable wealth of complications. It emphasizes collaboration, critical, of course, with the endoscopist, even with the radiologist who, in addition to laying the groundwork for the definition of indications, is directly implicated in the satisfactory development of the procedure during and after his implementation. Conclusions: In patients with blocking colorectal tumor is feasible to implement an attempt endoscopic decompression useful to the recovery of the intestinal canalization.